PENGARUH PERENDAMAN EKSTRAK DAUN MELINJO (Gnetum gnemon. L) TERHADAP BOBOT TELUR AYAM RAS (Gallus domesticus) - Hafnati Rahmatan; Asiah Asiah; Farah Fajarna (Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study was to determine the effect of ethanol extract of melinjo leaves on the weight of chicken eggs. The method used is the experimental method Completely Randomized Design (CRD) with 4 treatments and 6 replications. Data were analyzed by Variant Analysis and DMRT Advanced Test (Duncan Multiple Range Test ) at a significant level of 0.05, as well as quantitative descriptive analysis. The results showed that F count > F Table, it can be said that the extract of the leaves of Melinjo significantly affected the weight and shelf life of chicken eggs. Soaking the eggs using the most effective extract of melinjo leaf was used at the concentration of P3 (300,000 ppm). The best value P3 treatment after administration of ethanol extract of melinjo leaves and stored at room temperature for 21 days (Week III), namely at the value of egg weight = 51.17 grams from the initial weight of the egg 53 grams.. It can be concluded that the administration of ethanol extract of melinjo leaves had an effect on the weight and shelf life of race chicken eggs for 21 days with extract concentrations of 300,000 ppm.